Vivencias en tiempos de pandemia COVID-19 en familias con miembros diagnosticados con TEA, (Trastorno del Espectro Autista), en la ciudad de Cali. (2021)
The objective of this study was to describe the experiences in times of the COVID-19 pandemic in families with members diagnosed with ASD, (Autism Spectrum Disorder), in the city of Cali, more specifically to 3 families that are part of the APA Cali foundation. At the time of reviewing the literature, it was possible to notice that it is a relatively new topic and in some cases, the information was limited, and up to date, there is a study and research process by different universities around the world, these variables could be attributed to a new experience lived by humanity, for more than 100 years ago there had not been any global pandemic.